Response to antenatal HIV testing and prevention of parent to child transmission: an experience in a tertiary hospital in Chitwan, Nepal - Pokharel, SM; Abbas, H; Ghimire, A (Journal of College of Medical Sciences-Nepal, 2012)
The antenatal screening of HIV in all women is becoming an integral part of routine antenatal checkup in Nepal, by prevention of parent to child transmission (PPTCT) program. The aim was to analyze the response to implementation of PPTCT program in a peripheral hospital and to study the involvement of husbands for counseling and testing. Data of 3360 women attending the antenatal clinic from January 2010 to December 2010. Data of husband counseling and testing was also analyzed. Acceptability of the test after pretest counseling is 99 %. Women attended post test counseling and collected reports in 58.6%. Sero prevalence of HIV was 0.73% of which 62.5% came for post test counseling. Only 10 % of husbands of total antenatal cases came for counseling of which 6.6% got tested. The acceptability of the test after pretest counseling is satisfactory but the follow up for the post test counseling is to be improved. There is need to enhance male involvement to make husband friendly antenatal clinic. DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6707 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 36-38